Ekstraktivisme PT Freeport dalam Implementasi Corporate Social Responsibility melalui Yayasan Pemberdayaan Masyarakat Amungme dan Kamoro (YPMAK) - Zamharirah Sang Putri (Spektrum, 2026)
This study examines corporate power in natural resource governance through a critical analysis of Corporate Social Responsibility (CSR) implemented by PT Freeport Indonesia in Papua, focusing on the role of the Amungme and Kamoro Community Empowerment Foundation (YPMAK). The research employs Critical Management Studies (CMS) and Postcolonial Theory to analyze CSR as a mechanism of power. CMS is used to reveal how CSR policies and managerial practices reproduce power relations, depoliticize social conflict, and legitimize corporate dominance within global capitalism. Postcolonial Theory, drawing on Edward Said and Gayatri Chakravorty Spivak, helps identify the persistence of colonial legacies through resource control, top-down development discourses, and the marginalization of Indigenous knowledge. This study adopts a qualitative research method with an interpretive analytical approach, focusing on the interpretation of CSR discourses and practices as arenas of power relations. The analysis relies on secondary data, including corporate sustainability reports, CSR documents, regulatory frameworks, and civil society reports. The objective of this research is to critically assess CSR as a mechanism of legitimacy and social license to operate, and to evaluate whether CSR initiatives contribute to the fulfillment of the social, economic, and cultural rights of the Amungme and Kamoro communities. The findings indicate that Freeport’s CSR through YPMAK operates in a largely technocratic and reactive manner, prioritizing the management of social dissatisfaction over addressing structural issues such as customary land dispossession, environmental degradation, and political marginalization.